Management of acute diarrhea in children: is the treatment guidelines is really implemented? - Abbas, Jaigam; Chandra Pandey, Dinesh; Verma, Ashish; Kumar, Vijay (International Journal of Research in Medical Sciences, 2018)
Background: Acute diarrhea is a common problem in children especially in poor and developing nations. It is one of the leading cause of under-five years’ mortality globally. The children used to die each year of dehydration and electrolyte imbalance caused by acute diarrhea. Despite of WHO recommendations on the use of ORS and zinc in the management of acute diarrhea as a simple and effective treatment, the prescribing trend of ORS and zinc in acute diarrhoea is not up to the mark, which further increases the burden of the problems. Objectives: we aimed to assess; (1) prescribing trend of ORS and zinc in acute diarrhoea in children aged 6months to 5years by health care providers, (2) to asses’ proportion of patient education in acute diarrhea by health care providers. Methods: This was a qualitative, cross-sectional, hospital based study carried among children aged 6months to 5yrs. Results: This study was conducted among 313 children of acute diarrhoea who had been treated outside. Mean age (months) was 27.53±15.87. Out of all children who were treated from outside, 180 (57.50%) took treatment from general physician, 113 (36.10%) children took the treatment from pediatrician, and 20 (6.85%) took the treatment from the physician and 25 (7.9%) took treatment as over the counter antidiarrheal by the pharmacists. Out of them dehydration was documented only in 97 (30.99%), while ORS was given in 229 (73.16%) and zinc was given in 121 (38.65%) children. Patients education was done in 39 (12.46%). Conclusions: There was gross under implementation of treatment guidelines in the management of acute diarrhea by health care providers especially by general physicians.